Breaking law of overburden rock and key mining technology for narrow coal pillar working face in isolated island - Du Feng; Li Zhenhua; Li Songtao; Li Xiaolei; Li Guodong; Fan Xuan; Ren Hao; Cao Zhengzheng (Scientific Reports)
Abstract When conducting retreat mining in segmented coal pillars, the dynamic evolution of stress and overlying strata structure is more complex than conventional working faces due to the influence of adjacent working faces. Understanding and mastering the dynamic evolution patterns of overlying strata structure after retreat mining in segmented coal pillar working faces is essential for guiding the safe recovery of coal pillar resources under similar conditions. Through statistical analysis of the types of residual coal and the mining techniques, the current research status of residual coal mining system in China has been summarized. Based on the safety recovery technology system for multi-type residual coal pillar resources at Zhaogu No.2 Mine, this paper focuses on narrow coal pillar working faces in sections with fully mined-out areas on both sides. By using research methods such as on-site measurement, theoretical analysis, numerical simulation, and engineering experiments, starting from the stress state analysis and evolution law of coal seam mining, the dynamic evolution law of the overlying rock structure of sectional coal pillars has been mastered. On this basis, a stress arch mechanical model of the mining area is constructed, and the working resistance of the support is calculated and determined, ensuring the safe recovery of the working face. The research results show that before the backfilling of the sectional coal pillar working face, the working face is affected by the overlapping mining of the goaf on both sides, presenting a “bimodal” stress distribution pattern, with a stress concentration coefficient between 1.78 and 3.2. After the extraction of segmented coal pillars, stress arches consisting of high-stress zones form along both the strike and dip of the working face. The structural support provided by stress arches undergoes a dynamic evolution process of “formation-development-elevation-stabilization” as the working face advances. Following the instability and rupture of the lower basic roof hinge structure, the stress-bearing structure shifts to the higher basic roof, continuing to provide support for the surrounding rock stress in the mining space of the working face. A stress arch mechanical model for the dip and strike of the mining area is constructed , and the shape characteristics of the overlying rock stress arch in the coal pillar working face is mastered. Based on the stress distribution law and stress arch evolution characteristics of the surrounding rock of the coal pillar working face, the maximum working resistance of the support in the working face is theoretically calculated to be 9153.48kN. Compared with the measured mine pressure data, the selected support effectively ensures the safety production of the working face.